(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Teachers are dedicated to teach reading and copying in the classroom, with evaluations requiring comprehension of reading and responses to questionnaires, such as intraverbals, that test something other than what is taught. This study followed a case in which a teenager presented difficulty in the intraverbal response agreed as the appropriate response in the test. From the reference of Behavioral Analysis, a hypothesis was raised that the verbal repertoire requested in the test (written intraverbals), was not the same performed when studying (subvocal reading), and that making these functionally interdependent operants would condition the student to present an effective response in conditions similar to those of the test. The intervention was performed in four phases. Results demonstrate that the use of different verbal operants while studying create conditions for establishing interdependences that can improve academic performance.